Biosynthetic Studies on Water-Soluble Derivative 5c (DTX5c) - José J. Fernández; Tamara S. Vilches; Manuel Norte; Antonio Hernández Daranas (Marine Drugs, 2012)
The dinoflagellate Prorocentrum belizeanum is responsible for the production of several toxins involved in the red tide phenomenon known as Diarrhetic Shellfish Poisoning (DSP). In this paper we report on the biosynthetic origin of an okadaic acid water-soluble ester derivative, DTX5c, on the basis of the spectroscopical analysis of 13C enriched samples obtained by addition of labelled sodium [l-13C], [2-13C] acetate to artificial cultures of this dinoflagellate.